If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23 + 7x = -2(-3x + -6) + 8x Reorder the terms: -23 + 7x = -2(-6 + -3x) + 8x -23 + 7x = (-6 * -2 + -3x * -2) + 8x -23 + 7x = (12 + 6x) + 8x Combine like terms: 6x + 8x = 14x -23 + 7x = 12 + 14x Solving -23 + 7x = 12 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -23 + 7x + -14x = 12 + 14x + -14x Combine like terms: 7x + -14x = -7x -23 + -7x = 12 + 14x + -14x Combine like terms: 14x + -14x = 0 -23 + -7x = 12 + 0 -23 + -7x = 12 Add '23' to each side of the equation. -23 + 23 + -7x = 12 + 23 Combine like terms: -23 + 23 = 0 0 + -7x = 12 + 23 -7x = 12 + 23 Combine like terms: 12 + 23 = 35 -7x = 35 Divide each side by '-7'. x = -5 Simplifying x = -5
| 2m+14=-4 | | H=t^2-6t-12 | | 28=2w+2l(6w) | | -7(x-7)=3x-11 | | 242.25=(x+4.20)19 | | -37+2x=-4(x+4)-3 | | T-183.4=-109.8 | | (10x-61)+(x+10)=180 | | -5.6(x-4.25)=22.4 | | 4000/15/2 | | 12,197.8(y-1971)+44,000=425,000 | | -16+2b=b-8 | | 1.2=2/3(b-5) | | 83=-5x+3(1+7x) | | (27x^(3/4))^(2/3) | | 67.2=6(m+2.8) | | 54=3h-6+h | | -112=-7(-5x+6) | | 70x+6=50x-29 | | 880=(x+25)11 | | 11x-15=5x-13 | | -7(x+8)=-23+4x | | 9x+8y=-30 | | -6.5(4y+6)-1.1(3y-5)= | | 4000/7.5 | | 15-7x=96 | | R(t)=400(1.02)t | | 6(1+7x)=40+8x | | 3(z-3)=5(z+3)-12 | | -8x+9y=23 | | 5-21/8 | | 6x+3=-9x-13 |